Blockchain and AI Integration in Halal Supply Chains: Toward a Trusted Digital Ecosystem - Julian, Fajar Azhari; Rachmayani, Novianti; Aufi, Irwan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The halal supply chain plays a crucial role in ensuring compliance with Shariah principles and maintaining consumer trust in global markets. However, conventional certification systems often face limitations, including fragmented documentation, inefficiencies, and vulnerability to fraud and mislabeling. This study explores the potential integration of blockchain and artificial intelligence (AI) to address these challenges and develop a trusted digital ecosystem for halal supply chains. Employing a qualitative library research method, the study systematically reviews academic literature, industry reports, and regulatory documents published between 2020 and 2025. The findings reveal that blockchain enhances transparency and traceability through immutable record-keeping, while AI contributes predictive analytics, anomaly detection, and operational optimization. Although both technologies have been studied separately, their combined application in halal supply chains remains underexplored. This research proposes a conceptual framework for integrating blockchain and AI to reinforce halal assurance, streamline certification processes, and improve supply chain resilience. The study contributes to the academic discourse on halal supply chain governance and provides insights for policymakers, certification bodies, and industry practitioners seeking to establish a secure, ethical, and sustainable halal digital ecosystem.